Community Empowerment in Tourism in Lake Lengkong of Panjalu, Ciamis, West Java - Irfan Agustin; Rully Khairul Anwar (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2023)
Empowerment programs in the community will be prosperous and fulfill their life needs. The development of Lake (Situ) Lengkong Panjalu tourist object that along with the development of this tourist object has had an impact on social changes in the Panjalu Village community, especially in terms of social and economic. This change is based on the empowerment program in the tourism sector planned by the Panjalu Village government. The findings in the study show that the people of Panjalu Village before the existence of one of the empowerment programs, namely efforts to improve the welfare of the village community in the field of tourism, the community's economy has not improved. It tends to be below standard because it relies on the agricultural sector, including farming and fishing. However, after a community empowerment program and making the Lake a tourist attraction, the community's economy increased because it did not rely only on the agricultural sector; the people of Panjalu Village began to prosper and reduced unemployment then their lifestyle changed. Along with the development of human civilization, there have been changes in human life. As well as the village's asset income increases as tourists continue to visit Lake Lengkong Panjalu.